(untitled) (International Educators Conference, 2025)
The representation of women in historical literature is a central concern in both literary criticism and translation studies. In Uzbek historical novels, female figures, particularly queens, function not only as participants in political and social events but also as symbolic embodiments of morality, spirituality, and cultural values. This paper examines the image of queens in Pirimqul Qodirov’s celebrated historical novel Yulduzli tunlar (Starry Nights), focusing on the lexical, stylistic, and semantic peculiarities of their depiction. Through comparative analysis of the Uzbek original and its translations, the study highlights how female characters are reinterpreted in cross-cultural contexts. The findings reveal that while Qodirov constructs queens such as Qutlug Nigar Khanum, Khanzada Begim, and Robiya as multidimensional figures, translations often simplify their images, reducing moral dignity to physical beauty and spirituality to fragility. The paper concludes that greater cultural sensitivity and translator awareness are needed to preserve the authenticity of female representations in Uzbek historical literature for international readers.